Cost Oriented Humanoid Robot communication with IoT devices via MQTT and interaction with a Smart Home HUB connected devices. Issue 25 (2019) - Chivarov, Stefan; Kopacek, Peter; Chivarov, Nayden
Abstract: The article describes different approaches for connecting the teen sized humanoid robot Archie with IoT devices. Main goal of the project is to develop a cost oriented autonomous humanoid robot to assist humans in daily life tasks, thus Archie robot's natural habitat will be our homes and workplaces. Methods for ROS integration of remote internet enabled sensors, actuators and other devices are described. Test with real life use cases are performed. MQTT M2M protocol have been used for connecting to internet enabled IoT devices. Smart home hubs, which connect either locally or to the cloud, IoT devices, that use the Zigbee or Z-Wave and other protocols, rather than only Wi-Fi connected devices, are disused. Finally, we have successfully implemented and tested 3 different approaches for connecting Archie robot to IoT devices, which gives the robot the ability to interact with the environment by receiving data and the ability to control the thousands of IoT devices available on the market.